Emansipasi Perempuan pada Masa Muhammad Saw - Hermawati Hermawati (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The role of women is still often marginalized to this day. This occurs due to interpretations of texts, both religious and otherwise, that are gender biased. Mainstream masculinity has hegemonized consciousness, even among women themselves. It is not surprising that among women, some are submerged while perpetuating the hegemony of masculinity, alienating themselves from historical centers. Yet history also shows that significant roles of women are recorded amidst the hegemony of men. At the very least, the endeavors of women during the time of Prophet Muhammad (PBUH) demonstrate that women have a historically significant domain no less important than that of men.